Effects of iron saturation on antibacterial activity of lactoferrin - WANG Zhenjie; ZHANG Kang; LIANG Li; XIONG Qingqing; DU Huahua (浙江大学学报. 农业与生命科学版)
The purpose of this study was to elucidate how iron-depleted and iron-saturated forms of lactoferrin (Lf) exert its antibacterial activity in vitro. Bacteria were divided into three groups by treated with different forms of porcine Lf: the control group (without addition of Lf), apolactoferrin (Apo-Lf, iron saturation is 6.9%) group and hololactoferrin (Holo-Lf, iron saturation is 100.0%) group. The results showed that: 1) Native Lf and Apo-Lf significantly inhibited the growth of Escherichia coli K88 and Staphylococcus aureus (P＜0.01), which was not observed in Holo-Lf group. 2) Apo-Lf exerted antibacterial effect by chelating iron, and iron supplementation could eliminate the inhibitory effect of Apo-Lf on E. coli K88. 3) Scanning electron microscope (SEM) results revealed that Apo-Lf damaged the surface membranes of E. coli K88 and S. Aureus. However, Holo-Lf showed no effect on all of tested bacteria. 4) Predicted three-dimensional structures showed that the structures of Apo-Lf and Holo-Lf were markedly different, and the active site of Apo-Lf was more likely to directly interact with bacteria. Taken together, Apo-Lf inhibited the growth of E. coli K88 and S. Aureus by chelating iron or destroying the surface of bacteria.